Engineering change: strategic planning to build a department culture of diversity, equity, and inclusion in mechanical engineering - Cheng, Susan J.; Ortiz-Ortiz, Alondra M.; Grosh, Karl (Frontiers in Education, 2025)
Although diversity, equity, and inclusion (DEI) interventions in science, engineering, and higher education are often discussed as being led at the individual or institutional level, departments can be an effective academic entity for creating meaningful culture change. One way a department can embark on this work is through strategic planning, which can help a diverse group of stakeholders come together to identify a set of goals and pathways for achieving those goals over a sustained amount of time. In this piece, we present an overview of the University of Michigan Department of Mechanical Engineering’s three-phase DEI strategic planning process, which involved proposing strategic planning, creating the strategic plan, and preparing for implementation of the plan. Guiding questions and lessons learned from this process are provided to help other departments create their own locally relevant strategic plans in DEI.